2021
DOI: 10.3390/foods10091984
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sensory Qualities in Eggs from Three Breeds Based on Electronic Sensory Evaluations

Abstract: The present study was conducted on three commercial laying breeder strains to evaluate differences of sensory qualities, including texture, smell, and taste parameters. A total of 140 eggs for each breed were acquired from Beinong No.2 (B) laying hens, Hy-Line Brown (H) laying hens, and Wuhei (W) laying hens. Sensory qualities of egg yolks and albumen from three breeds were detected and discriminated based on different algorithms. Texture profile analysis (TPA) showed that the eggs from three breeds had no dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…We found that W1S, W1W, W2S, W2W, and W5S displayed higher values than the rest of the sensors in both breeds, indicating that methane, inorganic sulfides, alcohol, sulfur organic compounds, and nitrogen oxides were the main aroma components of duck meat, and SG and FG duck meat samples had similar odor characteristics. Dong et al also found that these five sensors accounted for the majority of egg yolks and albumen [ 21 ]. Furthermore, the SG duck can be distinguished from the FG duck by LDA analysis, and the SG duck had a higher odor than the FG duck, especially in methane.…”
Section: Discussionmentioning
confidence: 99%
“…We found that W1S, W1W, W2S, W2W, and W5S displayed higher values than the rest of the sensors in both breeds, indicating that methane, inorganic sulfides, alcohol, sulfur organic compounds, and nitrogen oxides were the main aroma components of duck meat, and SG and FG duck meat samples had similar odor characteristics. Dong et al also found that these five sensors accounted for the majority of egg yolks and albumen [ 21 ]. Furthermore, the SG duck can be distinguished from the FG duck by LDA analysis, and the SG duck had a higher odor than the FG duck, especially in methane.…”
Section: Discussionmentioning
confidence: 99%
“…The sensory characteristics of hardboiled and scrambled eggs of laying genotypes are presented in [32]. The flavor scores from Beinong eggs were observed significantly (P < 0.05) higher than that of Hy-Line Brown and Wuhei eggs [15]. The hardboiled egg flavors might be varied due to differences in amino acid and fatty acid compositions [33].…”
Section: Sensory Characteristics Of Hardboiled and Scrambled Eggs Of ...mentioning
confidence: 99%
“…Besides, an electronic nose system could detect volatile compounds with higher sensitivity but less psychological perception ability than humans do [12]. Volatile compounds of products can be analyzed by a gas chromatography-mass spectroscopy (GC-MS) and had enhanced the sensory quality though highly expensive and less feasible for a practical application than panelist and consumer implicating for their merits and demerits [13] [14] [15]. Moreover, an electronic tongue system can characterize product taste and improve sensory precessions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Electronic nose (e-nose) technology, which can digitize the empirical odor expression, has been widely used in food industry and introduced into the field of TCM to evaluate product quality rapidly and objectively. [19][20][21][22] Combined with gas chromatography (GC) and e-nose technology, 23,24 the Heracles NEO ultra-fast gas phase electronic nose (Heracles NEO e-nose) is an advanced olfactive tool that can be used to separate and identify the volatile compounds in TCMs. The chromatographic peaks obtained by GC are regarded as markers which can be used to obtain overall information about volatile constituents (also known as fingerprinting).…”
Section: Introductionmentioning
confidence: 99%